2022
DOI: 10.1007/s11332-021-00893-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of physical activity among informal carers: a systematic review of international literature

Abstract: BackgroundPrevious research has found physical activity levels among carers are low, and that carers are at greater risk of physical inactivity than their non-carer counterparts. Alternatively, research also suggests providing care may be associated with higher levels of physical activity than the general population, due to physically active care duties. Overall, there is a need to better understand the physical activity levels of carers to develop appropriate interventions and policies to promote health and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Our findings that non-daily consumption of fruits and vegetables and insufficient physical activity are less common among less-intensive caregivers compared with intensive caregivers or non-caregivers are also confirmed by others ( 29 ). A recent systematic review ( 30 ) aimed at better understanding of physical activity of caregivers. The authors conclude that the current body of research is insufficient to assess whether informal caregivers are at higher risk for physical inactivity than non-caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that non-daily consumption of fruits and vegetables and insufficient physical activity are less common among less-intensive caregivers compared with intensive caregivers or non-caregivers are also confirmed by others ( 29 ). A recent systematic review ( 30 ) aimed at better understanding of physical activity of caregivers. The authors conclude that the current body of research is insufficient to assess whether informal caregivers are at higher risk for physical inactivity than non-caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding more specific research with caregivers, Marquez et al (2012) measured PA objectively with an accelerometer and found that caregivers were often active, even for short periods of 10 minutes each, resulting in a significant difference in their PA levels, such that they showed higher PA than that of non-caregivers (Marquez et al, 2012). As a result of their responsibilites for caring for individuals with disabilities and their higher PA even in short periods (Lindsay et al, 2022), we expected our caregivers in the CwPD group to be more active than those in the CwTD group. However, we found no significant difference in PA levels between groups, based on our measurement of PA through self-report on the IPAQ.…”
Section: Discussionmentioning
confidence: 99%
“…Caregiving, however, can negatively impact one’s physical, emotional, and behavioral health. The most common method to evaluate physical health is through physical activity (PA) (Ku & Ghim, 2022; Lambert et al, 2016; Longacre et al, 2021; Lİndsay et al, 2022; Marquez et al, 2012); PA refers to any movement that requires energy expenditure by skeletal muscles, and PA has been shown to be an extremely important health-related variable (WHO, 2010) that is also relevant to the caregivers’ general experience. In the last two decades, expanded research on benefits associated with PA has confirmed the importance of participating in PA for people for all ages (Bull et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although a recent international review found mixed results with regard to differences between carers and non-carers in overall physical activity (which includes physical activity undertaken as part of the caring role), six studies focusing on leisure time physical activity (i.e. sport, exercise and physically active hobbies, rather than physical activity undertaken as part of one's occupation or caring duties) reported that carers engage in less leisure time physical activity than non-carers [19]. The authors of that review argue that whilst leisure time physical activity is beneficial to health, the physical activity involved in the caring role (e.g., cleaning, shopping, physical help, personal care) may be detrimental to health.…”
Section: Introductionmentioning
confidence: 99%